Critical Information Infrastructures Security First International Workshop, CRITIS 2006, Samos Island, Greece, August 31 - September 1, 2006 - Lopez, Javier. (Computer Communication Networks and Telecommunications ;, 2006)
Key sectors of modern economies depend highly on ICT. The information flowing through the resulting technological super-infrastructure as well as the information being processed by the complex computing systems that underpin it becomes crucial because its disruption, disturbance or loss can lead to high financial, material and, sometimes, human loss. As a consequence, the security and dependability of this infrastructure become critical and its protection a major objective for governments, companies and the research community. CRITIS has been born as an event that aims to bring together researchers and professionals from universities, private companies and public administrations interested or involved in all security-related heterogeneous aspects of critical information infrastructures. This volume contains the proceedings of the 1st International Workshop on Critical Information Infrastructure Security (CRITIS 2006), that was held between August 31 and September 1, 2006 on Samos, Greece, and was hosted by the University of the Aegean, Department of Information and Communication Systems Engineering, Laboratory of Information and Communication Systems Security (Info-Sec-Lab). In response to the CRITIS 2006 call for papers, 57 papers were submitted. Each paper was reviewed by three members of the Program Committee, on the basis of significance, novelty, technical quality and relevance to critical infrastructures. At the end of the reviewing process, only 22 papers were selected for presentation, resulting in an acceptance rate of 38%. Revisions were not checked and the authors bear full responsibility for the content of their papers.